The process of psychological training for the alpine skiing instructors - The role of the coach developer - Krawczynski, M.; Aschenbrenner, P.; Grzywacz, T.; Woznica, W. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
In the Polish system of training for Alpine skiing instructors the responsible person for teaching is a trainer/lecturer. Previously trainer/lecturer was oriented on improving their hard skills and at the same time undermining soft skills. One of the crucial components for the Alpine skiing instructors while their training is fitting them up with psychological competencies - soft skills (Erickson, Camire & Gilbert, 2021; Gilbert, 2017). The key challenge of modern education is to provide people with the tools to be flexible and open to constant changes and to prepare themselves to be creative and critical towards reality. In the presentation, the author describes the process of learning with the Theory of Experiential Learning - the so-called D.A. Kolb Cycle (Kolbe & Kolbe, 2022). It also highlights the need to transfer the teaching (academic) style to the workshop style in teaching skiing. It presents the main differences between the instructor (trainer) and the educator of other instructors (trainers) - coach developer. Instructor educators (coach developers) have the skills to develop, support and challenge other instructors (trainers) for longterm learning and development (Gould & Mallett, 2021). Undoubtedly, the educator's activities should be an integral part of the training system of the training staff of each sports organization and result from the adopted development strategy of the organization. The presentation illustrates the issues discussed with the selected content of the Polish coach developer training for the Association of Ski Instructors and Trainers of Polish Ski Association (SITN PZN) involving skills in line with the recommendation of the International Sport Coaching Framework (ISCF) (2013) coaching competence and coach development based on six primary tasks undertaken by sport coaches: 1) Setting vision and strategy; 2) Shaping the environment; 3) Building relationships; 4) Conducting practices and preparing for competitions; 5) Reading and reacting to the field; 6) Learning and reflecting.